Saraf implication in the vascular remodeling. (10th June 2022) - Martin Bornez, M; Rosado, JA; Ordonez, A; Smani, T
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Agencia Estatal de Investigación Background: Orai1 and STIM1, molecular components of Store-Operated Calcium Entry (SOCE), have been associated with vascular smooth muscle cells (VSMCs) proliferation in vascular remodeling. Nevertheless, the role of SARAF (SOCE Associated Regulatory Factor), a regulatory protein involved in STIM1 inhibition, has not been firmly established in the vascular remodeling. Objetive: The aim of this study was to examine the role of SARAF and Orai1 in VSMCs proliferation and neointima formation after balloon injury of rat carotid arteries. Methods and Results: Experiments were conducted in an animal model of rat carotid angioplasty to characterize neointima formation. VSMC isolated from rat coronary artery was also used to examine cell proliferation. The formation of neointima after balloon injury of rat carotid arteries was confirmed by haematoxylin and eosin staining of tissue sections up to 3 weeks after surgery. Injured arteries showed significant higher expression of SARAF, STIM1 and Orai1 compared to control tissues, corroborating the presence of these regulatory proteins in the neointima layer. Proximity ligation and co-immunoprecipitation assays revealed that SARAF interacts with Orai1 in the neointima. Furthermore, selective silencing of SARAF and Orai1 by small interfering RNA (siRNA) inhibited VSMC proliferation. Conclusions: Our data suggest that SARAF is involved in VSMC proliferation and neointima formation after vascular injury.